Public Sector Borrowings of Select States: Issues and Challenges - Gupta, Manish; Azharuddin, S.K.; Mahesh, Malvika (Economic and Political Weekly, 2025)
The public sector borrowing requirements for select Indian states are ascertained, with the objective of deriving a realistic estimate. It is of the view that instead of focusing on a narrow definition of fiscal indicators like debt and deficit, a broader
Keywords: Economic Uncertainties; Fiscal Deficit; Public Sector Borrowings